Fighting techniques of the imperial age 1776-1914 equipment, combat skills and tactics - Bruce, Robert B. (Robert Bowman) 1963; Jestice, Phyllis G.; Reid, Stuart; Rice, Rob S.; Schneid, Frederick C. (Amber Books, 2009)
An essential guide for military buffs and a comprehensive re - source for a transitional period in military history, Fighting Techniques of the Colonial Age shows in detail the methods by which European armies gained and lost ascendancy on the battlefields of the colonial era. From the tactics required to win battles in a period when op - ponents were often either heavily mismatched in technology, or employed entirely different strategies to outwit each other, Fighting Techniques of the Colonial Age explores this dynamic period of military history in full, covering campaigns including The Revolutionary War , The War of 1812, The Mexican War, the Crimean War , the Austro-Prussian War, the Franco-Prussian War, the Zulu War, the Sudan campaign, the Boer War and the Russo-Japanese War